Plan de capacitación para el Gobierno Autónomo Descentralizado Municipal del cantón las Naves, provincia de Bolívar - Landívar Triviño, Rocio Piedad (2012)
The country lives intense changes in the administrative, political, scientific, economic, social and financial, for that a reason the entities of the publish sector they should be met to stay to the even one with this changes, reason that the present investigation work incites to execute plans of training that allows to administrators, employees, public servants to be more efficient in the attention to the user. In this manner it justifies autonomous Government canton Las Naves´, a program of integral training is implemented as much authorities as to officials and employees, there is constituted like a source of cultural and academic enrichment that can serve from guide to the people interested in carrying out similar works. The results obtained of this work investigation threw data that, for this reason, think a personal solution for improving the quality of services to the users and interpersonal relationships and self-esteem of authorities and personal. The consulted material is in agreement with the thematic to investigate, with scientific literature of the moment. The proposal of elaboration of a training Plan will constitute in a very necessary work tool, because wither training it was possible to revert the state of down grade.